An Examination of Environmental Degradation Rooted in the Values of Lobha, Dosa, and Moha in Buddhism - Pratiwi, Puspita Setiya; Utami, Diah Wahyu Tri; Azkiya, Annisa Ahmad; Afifuddin, Muhammad Nizam; Hidayatullah, Ahmad Fauzan; Sidik, Muhammad Aunurrofiq (IAIN Palangka Raya, 2024)
Environmental degradation is largely caused by human actions. The study aimed to analyze environmental damage and its correlation with the three pillars of evil in Buddhism: lobha (greed), dosa (hatred), and moha (delusion). The research employed a qualitative method with a phenomenological approach to describe the research subjects through field research, involving observation, documentation, and interviews. The findings showed that the Buddhist belief in the three pillars of evil—lobha, dosa, and moha—is considered the root cause of environmental destruction. Humans often disregard their surroundings, showing indifference that fosters arrogance, leading to unwise behavior towards environmental sustainability. In response to environmental degradation, Buddhism offers measures to preserve the environment by teaching good moral ethics, which not only relate to human interactions but also to their relationship with nature. Furthermore, awareness is regarded as the key principle that individuals must embrace to overcome the three circles of evil: lobha, dosa, and moha.